Civil war and agrarian unrest : the Confederate South and southern Italy - Dal Lago, Enrico (Cambridge University, 2018)
"Between 1861 and 1865, both the Confederate South and Southern Italy underwent dramatic processes of nation-building, with the creation of the Confederate States of America and the Kingdom of Italy, in the midst of civil wars. This is the first book that compares these parallel developments by focusing on the Unionist and pro-Bourbon political forces that opposed the two new nations in inner civil conflicts. Overlapping these conflicts were the social revolutions triggered by the rebellions of American slaves and Southern Italian peasants against the slaveholding and landowning elites. Utilizing a comparative perspective, Enrico Dal Lago sheds light on the reasons why these combined factors of internal opposition proved fatal for the Confederacy in the American Civil War, while the Italian Kingdom survived its own civil war. At the heart of this comparison is a desire to understand how and why nineteenth-century nations rose and either endured or disappeared"-